Bifidobacterium Treated by Electrostatic Spray Drying Relieved Constipation by Changing the Relative Abundance of Bacteria Associated With Gastrointestinal Regulatory Peptides - Jiang, Tian; Lu, Wenwei; Fang, Zhifeng; Wang, Hongchao; Zhu, Jinlin; Zhang, Hao; Zhao, Jianxin (Frontiers in Cellular and Infection Microbiology, 2022)
In this study, three different microencapsulation methods were used to embed Bifidobacterium to explore the alleviating effects of embedding methods on constipated mice. By measuring the defecation related parameters, it was found that the bifidobacteria treated by electrostatic spray drying had the best ability to relieved constipation. Furthermore, by detecting constipation-related gastrointestinal regulatory peptides, inflammatory factors, intestinal microbiota and SCFAs, it was discovered that bifidobacteria treated by electrostatic spray drying changed the composition of intestinal microbiota, especially the relative abundance of bacteria that were positively correlated with AQP3, but negatively correlated with ET-1 and SS, then increased the level of AQP3 in the intestine, and finally relieved constipation by increasing fecal water content and small intestinal propulsion rate. In conclusion, the electrostatic spray drying method was superior to the other two methods in maintaining the activity of bifidobacteria, and relieved constipation by changing the relative abundance of bacteria that were correlated with gastrointestinal regulatory peptides and increasing the content of faecel water and small intestinal propulsion rate.